Synthesis, Thermal Properties and Nucleating Effect of N, N, N, N'-Tetra(benzoyl) Ethylene Diamine Tetraacetic Acid Dihydrazide as Nucleating Agent of Poly(L-lactic acid) - Yan-Hua Cai (E-Journal of Chemistry)
N, N, N, N'-Tetra(benzoyl) ethylene diamine tetraacetic acid dihydrazide as nucleating agent of Poly(L-lactic acid) (PLLA) was synthesized from benzoyl hydrazine and tetraacetic acid by acylation and ammoniation. and the structure of this novel tetraamide compound had been characterized by FT-IR. The thermal stability of N, N, N, N'-Tetra(benzoyl) ethylene diamine tetraacetic acid dihydrazide was investigated by TGA thermal analyzer. The result showed good thermal stability of N, N, N, N'-Tetra(benzoyl) ethylene diamine tetraacetic acid dihydrazide under 170 °C. N, N, N, N'-Tetra(benzoyl) ethylene diamine tetraacetic acid dihydrazide modified PLLA sample was prepared by a melt-mixing technique. With incorporation of 0.5% N, N, N, N'-Tetra(benzoyl) ethylene diamine tetraacetic acid dihydrazide, Non-isothermal crystallization behavior at different cooling rate showed the crystallization peak of PLLA became sharper and shift to higher temperature, and indicated that the presence of N, N, N, N'-Tetra(benzoyl) ethylene diamine tetraacetic acid dihydrazide accelerated the overall PLLA crystallization.